Determination of Surgical Nurses’ Compliance with Isolation Precautions - Ayşe Gökce Işıklı; Ümmü Yıldız Fındık (Dubai Medical Journal)
Introduction: Patients are impacted by healthcare-associated infections. The aim of the study is to determine the compliance status of surgical nurses to isolation precautions. Methods: This research is a descriptive and cross-sectional research. The research was carried out between July and September 2022 in two training and research hospitals, with the participation of 215 surgical nurses. Face-to-face interviews were used to collect the research data using the Nurse Information Form and the scale. Results: The mean score of the Scale of Compliance with Isolation Precautions was determined as 53.38 ± 4.45 over 18–90 points. Upon comparing the total mean scores of surgical nurses on the scale by gender, the compliance of female surgical nurses with isolation precautions was found to be higher compared to male surgical nurses (p < 0.05). Conclusion: The compliance of the surgical nurses participating in the study with isolation precautions was determined to be moderate. The compliance of surgical nurses with isolation precautions should be increased.